Intraoral Scanning Versus Conventional Methods for Obtaining Full-Arch Implant-Supported Prostheses: A Systematic Review with Meta-Analysis - Fernanda L. Vieira; Maísa Carnietto; José R. A. Cerqueira Filho; Ester A. F. Bordini; Hiskell F. F. Oliveira; Thiago A. Pegoraro; Joel F. Santiago Junior (Applied Sciences)
There is still no consensus on whether intraoral scanning for producing full-arch implant-supported prostheses is effective. Therefore, this systematic review aimed to analyze clinical studies that evaluated intraoral scanning versus conventional impression to obtain rehabilitation of full-arch fixed prostheses and removable. Registration was carried out in the PROSPERO database (CRD: 42020152197). Searches were performed in 11 databases. Review Manager 7.2 (2024) software was used for the quantitative analysis stage (α = 0.05). Bias analysis was conducted using the ROBINS-I and ROB scales, and the certainty of the evidence was evaluated using the GRADE scale. The initial search showed 33,975 abstracts and titles, from which, after applying the inclusion/exclusion criteria, 11 clinical studies were selected. Based on the studies collected, it was observed that there was no difference in the comparison between the digital (DG) and conventional (CG) groups for the following criteria: technical and biological complication rates and marginal bone loss (p > 0.05). The analysis of clinical execution time highlights a notable advantage of the DG over the CG at both scanned patient and implant levels (p < 0.05). Nevertheless, CG achieved fewer retakes than the DG (p < 0.05), demonstrating its reliability in execution. It is concluded that the survival rates of full-arch fixed prostheses produced using intraoral scanning are comparable to those achieved with traditional impression techniques, providing a reliable option for patients. However, further clinical studies are necessary due to the variability in clinical protocols.